2004
DOI: 10.1097/00126334-200402010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HIV Testing of Women in Labor

Abstract: For HIV-infected women who have not received antiretroviral treatment or transmission prophylaxis in pregnancy, starting antiretrovirals in labor or soon after birth can still decrease the risk of perinatal transmission. There is, therefore, potential benefit in conducting rapid HIV testing in labor, but hospitals are seldom prepared to conduct such testing. We compared protocols for rapid HIV testing at 2 hospitals to determine what proportion of women had results back early enough to intervene if results had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…However, this is not always feasible and many pregnant women first present to the health care system at the time of labor, and therefore their HIV serostatus is not known [32,33]. The availability of rapid tests allows for HIV testing to be conducted at the time of labor thus allowing the knowledge of the mother's HIV-status which provides a "window of opportunity" for interventions to reduce HIV-perinatal transmission [34,35].…”
Section: Labor and Delivery Wardsmentioning
confidence: 99%
“…However, this is not always feasible and many pregnant women first present to the health care system at the time of labor, and therefore their HIV serostatus is not known [32,33]. The availability of rapid tests allows for HIV testing to be conducted at the time of labor thus allowing the knowledge of the mother's HIV-status which provides a "window of opportunity" for interventions to reduce HIV-perinatal transmission [34,35].…”
Section: Labor and Delivery Wardsmentioning
confidence: 99%
“…Point-of-care rapid testing during labor enables providers to take effective, expedient measures to prevent perinatal HIV transmission (ACOG Committee on Obstetric Practice, 2004; Bulterys et al 2004;Centers for Disease Control and Prevention 1994;Cohen et al 2003;Forsyth et al 2004;Guay et al 1999;Kelen et al 1999), and rapid testing of source patients after occupational exposure facilitates employee decisions about post-exposure prophylaxis (Landrum et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid HIV testing programs have successfully delivered point-of-care test results in a variety of settings including labor and delivery, outpatient clinics, and emergency rooms. [13][14][15][16] Experience with rapid HIV testing in jails is limited. One recent study showed rapid testing in a jail was feasible but had a relatively low acceptance rate.…”
Section: Introductionmentioning
confidence: 99%